PERAN CAR, BOPO DAN NPL TERHADAP ROA PADA INDUSTRI PERBANKAN KONVENSIONAL - Veronika Joan Jasmine; Andi Hasryningsih Asfar; Sabrawijaya Sabrawijaya (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study is to determine the involvement between Capital Adequacy Ratio, Operating Expenses of Operational Income and Non Performing Loans to Return On Assets The research method used is a quantitative descriptive method, a population of 42 conventional banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period, sampling techniques using purposive sampling so that a sample of 8 companies was obtained. The results of hypothesis testing, the t-test of the CAR calculated tcount < ttable (-0.767 < 2.045) with a significant level (0.449 > 0.05), meaning that there is partially no affect between CAR and ROA. Meanwhile, BOPO has a calculated value of tcount > ttable (-9,683 > -2,045) with a significant level (0.000 < 0.05), it means that the BOPO partially affect the ROA. Then NPL has a calculated value tcount < ttable calculation (1,664 < 2,045) with a degree of significance (1,107 > 0.05) it means that partially NPL has no affect to ROA. For the F-test, it’s obtained that  fcount >   ftable (34,370 > 5.41), with a significance value of 0.000 < 0.05, it means that there is a significant effect between CAR, BOPO and NPL together on ROA.The conclusion is that partially CAR and NPL has no effect with ROA, BOPO partially has a negative effect with ROA, and simultaneously CAR, BOPO and NPL affect ROA